2011
DOI: 10.1111/j.1467-7687.2011.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between the other and me: the functional role of motor resonance and action effects in infants’ imitation

Abstract: This paper investigates a two-stage model of infants' imitative learning from observed actions and their effects. According to this model, the observation of another person's action activates the corresponding motor code in the infants' motor repertoire (i.e. leads to motor resonance). The second process guiding imitative behavior results from the observed action effects. If the modeled action is followed by a salient action effect, the representation of this effect (i.e. perceptual code) will be associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 59 publications
5
53
2
Order By: Relevance
“…No differences in imitation level should occur in the hands-free condition. In contrast, the two-stage model of infant imitation [18] would predict similar imitation rates in both trials in both conditions, as the action effect stays constant across demonstrations and no change takes place between trials which would improve infants' ability to map the observed action onto their own motor repertoire in the second trial.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…No differences in imitation level should occur in the hands-free condition. In contrast, the two-stage model of infant imitation [18] would predict similar imitation rates in both trials in both conditions, as the action effect stays constant across demonstrations and no change takes place between trials which would improve infants' ability to map the observed action onto their own motor repertoire in the second trial.…”
Section: Introductionmentioning
confidence: 85%
“…This would be in line with the principles of the mentalistic account [14], as the increase in the imitation rate might suggest infants' interpretation of the repeated demonstration of the unusual target action in the second trial as an emphasis on the intentional nature of the modeled action. This increase in imitation rates would, however, not be predicted by the teleological [12], the perceptual distraction account [20], or the two-stage model of infant imitation [18], as the model's rationality, motor action, or the appearance of the blanket did not change between trials. In the hands-occupied condition, the similar imitation rates in the first and second trial within the first 20 seconds provide support for the mentalistic [14] and the teleological account [12] and could also be explained by the two-stage model of infant imitation [18], as the model's physical constraints remained constant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations